BRIC AS THE NEW ECONOMIC POWER AND ITS CRITICISM TO THE DOMINATION OF G8 IN THE WORLD ECONOMY - Sat Fitrianingsih (2011)
This paper explores about BRIC as the new economic power and its criticism to the domination of G8 in the world economy. BRIC criticizes the existence of G8 because the domination of the G8 members in decision making process in the world and of the spread of their regime and power is not relevant with recent world economy. This research purpose is not only showing the effort of each BRIC country to be BRIC members, but also to explore the efforts of BRIC to be the new economic power in the worl